Báo cáo tóm tắt tình hình sản xuất công nghiệp và hoạt động thương mại 6 tháng đầu năm 2009 - Bộ Công thương (2009)
Báo cáo tóm tắt tình hình sản xuất công nghiệp và hoạt động thương mại 6 tháng đầu năm 2009